Vengeance Zero (An Agent Zero Spy Thriller-Book #10) - Jack, Mars (Lukeman Literary, 2020)
"You will not sleep until you are finished with AGENT ZERO. A superb job creating a set of characters who are fully developed and very much enjoyable. The description of the action scenes transport us into a reality that is almost like sitting in a movie theater with surround sound and 3D (it would make an incredible Hollywood movie). I can hardly wait for the sequel." --Roberto Mattos, Books and Movie Reviews VENGEANCE ZERO is book #10 in the #1 bestselling AGENT ZERO series, which begins with AGENT ZERO (Book #1), a free download with nearly 300 five-star reviews. When a minor terrorist group, looking to make its mark, aims to take out a "soft target" in the United States-one relatively unguarded yet which can be hugely damaging to the U.S.-the race is on for Agent Zero to discover their object and stop them before it's too late. Yet Zero faces his own battles: when he is targeted for assassination and someone close to him ends up the victim instead, it sends his life into a downspin, and allows him only course of action: vengeance. Will Zero be able to save the target-and himself-before he spirals out of control? VENGEANCE ZERO (Book #10) is an un-putdownable espionage thriller that will keep you turning pages late into the night. Book #11 (ZERO ZERO) is also available. "Thriller writing at its best." --Midwest Book Review (re Any Means Necessary) "One of the best thrillers I have read this year." --Books and Movie Reviews (re Any Means Necessary) Also available is Jack Mars' #1 bestselling LUKE STONE THRILLER series (7 books), which begins with Any Means Necessary (Book #1), a free download with over 800 five star reviews!
Keywords: Dobrodružství, napětí, thrillery